Oriented construction of S-doped, exposed {001} facet BiOBr nanosheets with abundant oxygen vacancies and promoted visible-light-driven photocatalytic performance. Issue 44 (23rd October 2020) - Huang, Meina; Li, Ju; Su, Wenli; Huang, Xindi; Li, Bin; Fan, Minguang; Dong, Lihui; He, Haixiang
Abstract : S-doping orients the facet growth of BiOBr nanosheets from original exposed {010} plane towards {001}-dominant plane, resulting in narrower bandgap energy, higher efficient charges separation and oxygen vacancies (OVs) concentration. Abstract : Element doping and crystal engineering are efficient strategies to enhance the photo-reactivity of semiconductors by tuning the physico-chemical properties. Herein, S-doped BiOBr photocatalysts with tunable exposed {001} facets were prepared by a hydrothermal method and characterized by XRD, XRF, BET, FT-IR, SEM, TEM, EDS, XPS, UV-vis DRS, EIS, and EPR. It is revealed that S doping could orient the facet growth of BiOBr nanosheets from the originally exposed {010} plane towards the {001} dominant plane. Thiourea is selected as a "three-in-one" reaction medium, which not only acts as a kind of ligand, a capping agent and an S donor, but also plays a crucial role in the oriented growth of BiOBr nanosheets with exposed {001} facets. The photocatalytic activity of the obtained hybrids is evaluated by oxidizing RhB under visible light irradiation. S-Doped BiOBr catalysts show significant improvement in photocatalytic activity compared with original BiOBr, which is attributed to the synergistic effect of S doping and dominant {001} facet growth, resulting in narrower bandgap energy, more efficient charge separation and higher oxygen vacancy (OV) concentration. This study provides a paradigm of crystal facet control by element doping, and gives a deep insight into the specific surface area and properties determined by element doping and crystal facet engineering.